Subjective impressions under LED and metal halide lighting. (June 2014) - Kostic, A; Djokic, L
In order to compare subjective impressions created by LED and metal halide ambient lighting, a pilot project was conducted in a Belgrade park. All general requirements for an adequate comparison of subjective impressions were fulfilled. The survey was conducted using a questionnaire related to all aspects the researchers considered relevant for subjective evaluation of illuminated pedestrian paths in parks. It was concluded that the respondents, both those who had and those who did not have previous knowledge in the field of lighting, strongly preferred the use of metal halide lamps for the illumination of parks, which is in opposition to the statements of some LED manufacturers. It was also shown that light level and feelings of safety and comfort are evaluated as most important.